AN EMPIRICAL STUDY OF TRAINING AND DEVELOPMENT PRACTICES IN INDIAN BANKING SECTOR - Upadhyay, Anand; Sharma, Neha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research study is an attempt to identify the issues and challenges to concern with training and development practices in Indian banking sector. The issues associated with some of the major areas like employee morale, performance and productivity, lower cost production, lower turnover, and change management. This research problem refers to some exertion which a researcher experiences in a practical situation and wants to attain a solution for the same. In this research, the components of the research are the variables that contribute to employee’s perception towards training and development practices in banking sector. While formulating the research problem, research objectives and hypotheses that are framed to make it more appropriate in nature to bring out an ultimate solution to the prevailing issues. Probably particular studies on issues and challenges towards employees’ perception, training and development programs. This study is an effort to examine the imperative determinants and factors to concern with training and development. It will bring evidence on what effect the firm-specific factors, organization-specific factors and the general factors have on the training and developments programs. The Government, key officials of concern organization may have a deep insight to frame new policies for present and future. It is hoped that the outcome of this study will also provide an insight of the employees to understand over all functioning. This research work is very significant, path-finding and demonstrating in the human resource management in the banking sector. In this research work a breakthrough focus has been be given to qualitative and quantitative parameters to check the employees’ perception towards training and development programs.